Plate 09. View of Assmannshausen next to the castles Bauzberg and Falkenburg - Janscha, Laurens, 1749-1812 (artist):::::::::::::::; Ziegler, Johann (engraver)::::::::::::::: (Paul Harris; United Kingdom; Edinburgh, 2020)
Color engraving with a view of the town of Assmannshausen on the Rhine and the ruins of the castles Bauzberg and Falkenburg. The ruins here are from two castles that date back to the 11th century.